Pareto - Improving Unemployment Policies - Klaus Wälde; Jörg Lingens (University of Würzburg, Department of Economics, 2005)
We investigate how continental European unemployment can be reduced without reducing unemployment benefits and without reducing the net income of low-wage earners. Lower unemployment replacement rates reduce unemployment, the net wage and unemployment benefits. A lower tax on labour increases net wages and - for certain benefit-systems - unemployment benefits as well. Combining these two policies allows to reduce unemployment in countries with "net-Bismarck" and Beveridge systems without reducing net income of workers or the unemployed. Such a policy becomes self-financing under realistic parameter constellations when taxes are reduced only for low-income workers.
Keywords: J51; E60; J38; H23; 330; Inequality; Unemployment; Taxation; Policy reform